Identification of a novel AGO2 variant causing LESKRES in a Chinese family with intellectual disability - Yang, Shufa; Song, Wei; Yan, Yousheng (Frontiers in Genetics, 2025)
BackgroundLessel-Kreienkamp syndrome (LESKRES, MIM #619149), an autosomal dominant genetic disorder caused by variants in AGO2 (MIM*606229), primarily leads to neurodevelopmental symptoms.ObjectiveThis study aims to investigate the genetic etiology of a family with intellectual disability.MethodsWhole-exome sequencing (WES) was used to initially identify the pathogenic variants responsible for the intellectual disability in the family, and Sanger sequencing was employed for confirmation. Complete family information was collected, and Sanger sequencing was performed to confirm the co-segregation of the variant with the intellectual disability, thereby determining the pathogenicity of the novel variant. The pathogenicity of the novel variant was evaluated using in silico methods.ResultsAll four intellectual disability individuals carried the novel AGO2 (NM_012154.5): c.2149T>C (p.Cys717Arg) variant, while the other individuals did not. According to ACMG guidelines, this novel variant is classified as likely pathogenic. The novel variant occurs at a conserved position in AGO2 and is predicted to affect the 3D structure of the AGO2 protein.ConclusionThis study identifies a novel AGO2 variant causing LESKRES in the Chinese population for the first time. Our findings expand the variants spectrum of AGO2 leading to LESKRES and highlight the value of WES in diagnosing genetic causes of intellectual disabilities.